MO495: A Comparative Study of Patient Mortality During First and Second Waves of Covid-19 Pandemic in Dialysis Patients and Kidney Transplant Recipients. (3rd May 2022) - Vart, Priya; Jager, Kitty J; Arnol, Miha; Duivenvoorden, Raphaël; Franssen, Casper F M; Groeneveld, Marc; Hemmelder, Marc H; Lepeytre, Fanny; Malfait, Thomas; Midtvedt, Karsten; Mitra, Sandip; Facundo, Carme; et al.
Abstract: BACKGROUND AND AIMS: Patients on kidney replacement therapy (KRT) are at a particularly high risk of mortality from COVID-19. In this study, we investigated COVID-19 mortality in KRT patients in the first and second waves of the pandemic and potential reasons for any difference in mortality between the two waves. METHOD: Data from the European Renal Association COVID-19 D atabase (ERACODA) of KRT patients who presented between 1 March 2020 and 28 February 2021 with COVID-19 were analyzed. The cut-off for dividing the first and second waves was set for 1 August 2020. The primary study outcome was 28-day mortality. Multivariable Cox proportional-hazards regression analysis was used to examine the relationship between the pandemic waves and mortality with follow-up time starting at the date of presentation. Dialysis patients and kidney transplant recipients were analyzed separately. RESULTS: Among 3004 dialysis patients (1253 in the first and 1751 in the second wave), the 28-day mortality was 24.3% in the first wave and 19.6% in the second wave (P = .002). Compared with the first wave, in the second wave, identification of patients with limited to no symptoms was higher (14.3% versus 24.8%; P < .001), hospitalization was lower (71.3% versus 44.3%; P < .001), but in-hospital mortality was similar (30.4% versus 30.7%; P = .92) (Fig. 1 ). Crude hazard ratio (HR) for 28-day mortality in the second wave was 0.77 (95% CI: 0.66, 0.89). However, in a fully adjusted model, when correcting for differences in patient and disease characteristics, including the reason for COVID-19 screening and disease severity, the HR for mortality in the second wave was 0.93 [95% confidence interval (95% CI): 0.79–1.10]. When follow-up was chosen to start at the date of first symptoms to account for possible lead-time bias, crude HR for 28-day mortality in the second wave was 0.90 (95% CI: 0.75–1.07) and the fully adjusted HR was 0.98 (95% CI: 0.81–1.18). Among 1035 kidney transplant recipients (475 in the first and 560 in the second wave), results were essentially similar except that patients in the second wave were younger (55.6 years versus 58.2 years; P = .002), and crude HR for 28-day mortality from the date of first symptoms was 0.66 (95% CI: 0.47–0.93), whereas the fully adjusted HR was 1.02 (95% CI: 0.70–1.49). CONCLUSION: Among patients on KRT with COVID-19, 28-day mortality rates were lower in the second wave compared with the first wave. However, a greater proportion of patients with minimal symptoms, lead-time bias in dialysis patients, and younger age in kidney transplant recipients possibly explain the lower mortality during the second wave. Any improvement in patient management during the second wave may not be the main reason for lower mortality.